Parental and In-Laws Support: Correlation Study of Characteristics in Postpartum Mothers - Azamta, Fadila; Rahayuningsih, Faizah Betty (Universitas Muhammadiyah Surakarta, 2022)
Purpose: To describe the support of parents and in-laws, and to determine the correlation between characteristics and the support of parents and in-laws in postpartum mothers.Methodology: This type of research uses a quantitative descriptive method. In this study, data collection used a social support questionnaire by measuring the support of parents and in-laws. Respondents obtained for this study amounted to 61 postpartum mothers. Samples were taken by purposive sampling technique.Results: In this study, it can be described that support from parents is more often given to postpartum mothers. This can happen because respondents often contact their biological parents compared to contacting their parents-in-law. Most of the respondents live with their family of origin and their husband more than they live with their in-laws. Some of the characteristics in this study did not show significant results or had a weak relationship with the support of parents and in-laws. Only the categorical characteristics of working on parental support show that there is a significant relationship between working characteristics and parental support because the results of the P value show a value of p = 0,047. While other characteristics such as village, education level, marital status, ethnicity, living together, type of work, profession, intention to get pregnant, desire to get pregnant, complications, method of delivery, and baby nutrition showed insignificant results because the result was P value > 0,05.Applications/Originality/Value: The difference between this study with previous research lies in the research respondents, research time, measurement tools, literature used, the theory used, and research results.